Implementation of Configuration Management Virtual Private Server Using Ansible - I Putu Hariyadi; Khairan Marzuki (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2020)
Virtualization technology has been applied to universities with computer study programs to support practicum in Network Management courses. Each user gets a Virtual Private Server (VPS) with container technology. VPS system that is prepared manually requires a long time, especially when the number of users is increasing. The activity repeats every semester so it becomes ineffective and inefficient. Application of automation using Ansible can help to manage VPS objects in the Promox Virtual Environment (PVE) Cluster dynamically. Network Development Life Cycle (NDLC) was used as a method in this study. The design of the VPS management automation system created supports the grouping of container, user and permission resource management for users. The design is implemented in Ansible Playbook. The test results show the average time of making VPS objects per student with an automation system 2 (two) times faster, that is 26.25 seconds compared to the old system which takes 2 minutes 15 seconds. Besides that, the Playbook that was created succeeded in automating the start and stop containers per group of students based on the practicum schedule dynamically so as to maintain the availability of services from the PVE Cluster.